The impact of entrepreneurship knowledge on students' e-entrepreneurial intention formation and the moderating role of technological innovativeness - Pham Minh; Anh Tuyet Thi Nguyen; Duy Thien Tran; Tam Toai Mai; Vinh Trung Nguyen (Journal of Innovation and Entrepreneurship, 2023)
In the era of Industry 4.0, online entrepreneurship is gradually seen as an essential tool that brings innovative values to the integration and development of a country. The rapid failure of nascent businesses stemming from a lack of human capital directed this study to explore the role of students' knowledge and technological innovativeness in motivating students to form e-entrepreneurial intentions. Information collected from 405 students from universities in Vietnam via online questionnaires was analysed using SmartPLS 4 to test the relationships among seven factors proposed in the research model. The results show that entrepreneurial education and prior experiences are the foundation for improving students' perceived feasibility and usefulness, forming their entrepreneurial motivation. Next, entrepreneurial motivation becomes an important premise for promoting students' entrepreneurial intentions more effectively. Furthermore, the study found that students' technological innovativeness moderated the relationship between their entrepreneurial motivation and intention to set up a digital business.
Keywords: 650; E-entrepreneurial intention; Education; Motivation; Prior experience; Technological innovativeness